2014
DOI: 10.1371/journal.pone.0087268
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Analysis Reveals a Link between NDRG1 and Vesicle Transport

Abstract: N-myc downstream-regulated gene 1 (NDRG1) is induced by cellular stress such as hypoxia and DNA damage, and in humans, germ line mutations cause Charcot-Marie-Tooth disease. However, the cellular roles of NDRG1 are not fully understood. Previously, NDRG1 was shown to mediate doxorubicin resistance under hypoxia, suggesting a role for NDRG1 in cell survival under these conditions. We found decreased apoptosis in doxorubicin-treated cells expressing NDRG1 shRNAs under normoxia, demonstrating a requirement for ND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Although the clinical status of NDRG1 is well documented, mechanisms by which NDRG1 prevents metastasis remain poorly understood. We and others have shown that NDRG1 may function as a vesicular transport protein (Askautrud et al ., ; Kachhap et al ., ; Pietiainen et al ., ). In the present study, we provide molecular insights into the mechanism by which NDRG1 prevents prostate metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical status of NDRG1 is well documented, mechanisms by which NDRG1 prevents metastasis remain poorly understood. We and others have shown that NDRG1 may function as a vesicular transport protein (Askautrud et al ., ; Kachhap et al ., ; Pietiainen et al ., ). In the present study, we provide molecular insights into the mechanism by which NDRG1 prevents prostate metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its role in stress signaling, it also plays a role in vesicular trafficking. 69 V-type proton ATPase subunit E 1 (ATP6V1EJ) is a subunit of the peripheral V1 complex of vacuolar ATPase essential for assembly or catalytic function. A decreased level of a2 vacuolar ATPase, a member of the V-type ATPase could be used as a marker for infertility.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most important phenotype exhibited by NDRG1 nulls is demyelinating neuropathy (Okuda et al., ). Recent studies have demonstrated that NDRG1 is connected to intracellular vesicle transport (Askautrud et al., ). It functions as a Rab4a effector localized to the endosomes and is involved in the trafficking of low‐density lipoprotein receptor (LDLR) (Kachhap et al., ).…”
Section: Introductionmentioning
confidence: 99%